2015
DOI: 10.1177/070674371506001209
|View full text |Cite
|
Sign up to set email alerts
|

Successful Application of a Canadian Mental Health Curriculum Resource by Usual Classroom Teachers in Significantly and Sustainably Improving Student Mental Health Literacy

Abstract: Objective: To investigate whether the significant and substantive findings from a previous study of youth mental health literacy (MHL) could be replicated using the same methods in another population. Method:We examined the impact of a curriculum resource, the Mental Health and High School Curriculum Guide (The Guide), taught by usual classroom teachers on students' knowledge and attitudes related to mental health and mental illness in Canadian secondary schools. Survey data were collected before, immediately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 41 publications
9
92
0
3
Order By: Relevance
“…These recommendations are in good alignment with a recent MHL approach that is based on existing classroom friendly pedagogical applications that can be easily and inexpensively delivered within existing educational systems and does not require extracurricular or outside-of-school inputs [2,6]. When applied through enhancing capacity of classroom teachers to integrate evidence-based MHL curriculum resources (http://teenmentalhealth.org/curriculum/) into existing curriculum, as demonstrated by numerous Canadian studies, such interventions can concurrently result in positive MHL outcomes for both students and teachers alike [21][22][23][24]. Additionally, this approach can facilitate the development of an horizontally integrated school-based pathway to youth mental health care that links education and health systems, enhances identification, and facilitates triage and referral of students with mental disorders to local mental health care providers, thus functionally integrating educational and health care delivery systems, even in the absence of specific policies designed to do so [13,25].…”
mentioning
confidence: 99%
“…These recommendations are in good alignment with a recent MHL approach that is based on existing classroom friendly pedagogical applications that can be easily and inexpensively delivered within existing educational systems and does not require extracurricular or outside-of-school inputs [2,6]. When applied through enhancing capacity of classroom teachers to integrate evidence-based MHL curriculum resources (http://teenmentalhealth.org/curriculum/) into existing curriculum, as demonstrated by numerous Canadian studies, such interventions can concurrently result in positive MHL outcomes for both students and teachers alike [21][22][23][24]. Additionally, this approach can facilitate the development of an horizontally integrated school-based pathway to youth mental health care that links education and health systems, enhances identification, and facilitates triage and referral of students with mental disorders to local mental health care providers, thus functionally integrating educational and health care delivery systems, even in the absence of specific policies designed to do so [13,25].…”
mentioning
confidence: 99%
“…For example, medical research tends to favor a proven future interpretation. Thus, Kutcher, Wei, and Morgan (2015) concluded their study by noting that "these results [i.e., those obtained from their intervention] suggest a simple but effective approach to improving MHL [mental health literacy] in young people" (p. 580). Comparable inferences are found in studies investigating educational-type interventions.…”
Section: Three Research Designs Necessitating a Two-mean Comparison: mentioning
confidence: 99%
“…A large randomized controlled trial consisting of 534 students in the regional area of Ottawa showed that a curriculum-based programme delivered by usual classroom teachers was effective in improving student knowledge and attitudes towards mental health (Milin et al, 2016). Such improvements have also been shown to be maintained at the 2-month follow-up point (Kutcher, Wei, & Morgan, 2015), suggesting great potential in reducing stigma towards psychosis among the adolescent population.…”
Section: Reducing the Stigmamentioning
confidence: 99%